Analisis Faktor Penyebab Meningkatnya Angka Cerai Gugat di Mahkamah Syar’iyah Kutacane - Irda Djesra Mukhdalifa; Sukiati Sukiati; Dhiauddin Tanjung (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study was motivated by the increasing number of divorce petitions filed by wives at the Kutacane Syar’iyah Court in recent years, indicating challenges to family resilience and the effectiveness of resolving marital conflicts. This study aims to analyze the factors contributing to the rise in divorce petitions, examine their impact on society, and identify the judges’ considerations in deciding divorce cases at the Kutacane Syar’iyah Court. The research employed an empirical juridical approach. Data were collected through interviews with judges and court staff, case documentation, and literature review, and were analyzed using descriptive qualitative methods. The findings indicate that the increase in divorce petitions is influenced by several factors, including economic problems, husbands’ lack of responsibility, prolonged marital disputes, infidelity, domestic violence, and poor family communication. The increase in divorce petitions has social, psychological, and economic impacts on families, particularly on children's welfare. Judges base their decisions on facts presented during the trial, available evidence, applicable legal provisions, and the principle of public benefit to achieve justice for the parties involved. This study is expected to provide valuable input for strengthening family resilience and optimizing mediation efforts to reduce divorce rates.